L- ASPARAGINASE FROM STREPTOMYCES sp. ISOLATED FROM THE RHIZOSPHERE OF A PALM TREE, ITS SEPARATION, PURIFICATION AND ANTITUMOR ACTIVITY - MAGDA M. ALY; SAMYAH JASTANIAH; MOHAMMED GURBAN KUCHARI (International Journal of Pharma and Bio Sciences, 2013)
Screening procedure was initiated in an effort to find organisms that would produce higher yields of L-asparaginase (L-Asp). In this screening, 100 bacterial isolates were examined for L-Asp production. Eleven isolates produced L- Asp on modified M9 medium containing asparagine as nitrogen source and phenol red as an indicator. The diameter of the produced pink zone was ranged from 8.9 to 23.3 mm. In liquid medium, the isolate AFP47 was the most active isolate in intracellular L-asparaginase production with 4.73 U/mg dry cells. The isolate AFP47 was identified using morphological, physiological and chemical characters as Streptomyces sp AFP47. Identification was confirmed with 16S rDNA and similarity level of 99% was found to genus Streptomyces. L-asparaginase was extracted from the cells and purified using column chromatography. The purified enzyme has 140 kDa and exhibited antitumor activity against Leukemic target cell HL60 with LD50 of 150 U/ml.